Saint Lucia. Significant achievements 2020 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (2021)
The main activities carried out by the Institute in Saint Lucia during 2020 are identified, with respect to the needs and interests of the country, in favor of tourism and family farming. Likewise, among the achievements carried out, the progress of the different projects implemented, the extension activities in the dissemination of information with publications, forums, training and research are recognized. Finally, for the recovery of the COVID-19 situation, it contributes to generating technical inputs for the recovery from the pandemic.